Sistem Pembinaan Anak Binaan di Lembaga Pembinaan Khusus Anak (LPKA) Klas I Tanjung Gusta Medan - Sari Kartika Sembiring; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2019)
Abstract. The System of Practice embraced by Indonesia, regulated in Law No.12 of 1995 on Correctionalism gives meaning to the development of